Approaches to strategy and business models - Torres Castillo, Aníbal (2020)
The aim of this article is to develop the most relevant strategy approaches and the approaches related to business models, and to demonstrate the close link existing between both concepts. The theoretical referents are Michael Porter, Henry Mintzberg, Kim, and Mauborgne, Osterwalder and Pigneur, with focus on the strategy proposed by Igor Ansoff. We analyze the sequencing of the use of the various strategy approaches and the business models approaches, and the impact on each other. We end up by answering the query: What comes first, the strategy or the business model?